Galatians - Greene-McCreight, Kathryn. 1961- (Grand Rapids, Michigan : Brazos Press, a division of Baker Publishing Group, 2023)
"A respected theologian offers a theological reading of Galatians in this addition to the Brazos Theological Commentary on the Bible"--
Includes bibliographical references (pages 185-193) and indexes.
Keywords: Bible. -- Commentaries; Commentaries